Use of Android-Based Flipbook Educational Media to Increase Knowledge, Beliefs, Attitudes, and Intentions of Prospective Brides in Stunting Prevention in Semarang City - Lestari, Eva; Shaluhiyah, Zahroh; Adi, Mateus Sakundarno (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The prevalence of stunting in Semarang City is still relatively high. Low public knowledge about stunting prevention can increase the incidence of stunting. Stunting can be prevented before pregnancy. Prospective brides are strategic targets in stunting prevention so that they can prepare for a healthy pregnancy. Increasing the knowledge of the prospective brides can be done by providing education using media that follows the characteristics of the prospective brides, namely using Android-based flipbook media. Aims: The study aims to analyze the effect of education using Android-based flipbook media on increasing knowledge, beliefs, attitudes, and intentions of prospective brides in stunting prevention in Semarang City. Method: This study used a quasi-experimental research design with a nonequivalent control group design. The sample of the research was prospective brides totaling 94 people, consisting of treatment and control groups of 47 people. Data collection used pre-test and post-test questionnaires to measure prospective brides' knowledge, beliefs, attitudes, and intentions in stunting prevention. Results: The results showed that there were significant differences in the average knowledge score (p = 0.001), beliefs (p = 0.016), attitude (p = 0.001), and intention (p = 0.001) of prospective brides in stunting prevention. Conclusion: So it can be concluded that education about stunting prevention using Android-based flipbook media influences increasing knowledge, beliefs, attitudes, and intentions of prospective brides in stunting prevention. The greatest influence is shown on the knowledge variable, which is equal to 29,7%.